Degradation of tetrabromobisphenol A by a ferrate(vi)–ozone combination process: advantages, optimization, and mechanistic analysis. Issue 71 (17th December 2019) - Han, Qi; Dong, Wenyi; Wang, Hongjie; Ma, Hang; Gu, Yurong; Tian, Yu
Abstract : This study systematically investigated the ferrate(vi )–ozone combination process for TBBPA degradation. Abstract : This study systematically investigated the ferrate(vi )–ozone combination process for TBBPA degradation. Firstly, the advantages of a ferrate(vi )–ozone combination process were assessed as compared with a sole ozone and ferrate(vi ) oxidation process. Then, the performance of the ferrate(vi )–ozone combination process was investigated under different experimental conditions, including the dosing orders of oxidants, dosing concentrations of oxidants, and the initial solution pH. At the same time, toxicity control (including the acute and chronic toxicity) and mineralization were analyzed after optimization. Finally, a mechanism was proposed about the synergetic effects of the ferrate(vi )–ozone combination process for decontamination. The ferrate(vi )–ozone combination process proved to be an efficient and promising technology for removing TBBPA from water. After being pre-oxidized by ferrate(vi ) for 3 min and then co-oxidized by the two oxidants, TBBPA of 1.84 μmol L −1 could be completely degraded by dosing only 0.51 μmol L −1 of ferrate(vi ) and 10.42 μmol L −1 of ozone within 10 min in wide ranges of pH (5.0–11.0). Up to 91.3% of debromination rate and 80.5% of mineralization rate were obtained, respectively. In addition, no bromate was detected and the acute and chronic toxicity were effectively controlled. The analysis of the proposed mechanism showed that there might exist a superposition effect of the oxidation pathways. In addition, the interactions between the two oxidants were beneficial for the oxidation efficiency of ferrate(vi ) and ozone, including the catalytic effect of ferrate(vi ) intermediates on ozone and the oxidation of low-valent iron compounds by ozone and the generated ·OH radical.